2021
DOI: 10.1155/2021/6657434
|View full text |Cite
|
Sign up to set email alerts
|

Increased Oxidative Stress in Gastric Cancer Patients and Their First‐Degree Relatives: A Prospective Study from Northeastern Brazil

Abstract: Background and Aims. First-degree relatives of gastric cancer patients are at increased risk of developing gastric cancer. Increased oxidative stress, including lipid peroxidation, has been associated with gastric carcinogenesis. Whether first-degree relatives of gastric cancer patients have increased oxidative stress remains unknown. We aimed to compare oxidative stress in patients with gastric cancer, their first-degree relatives, and dyspeptic controls. Methods. A total of 155 patients undergoing upper endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…MDA levels were raised in both benign and malignant bone tumors as compared to healthy controls, though the rise in levels was more significant in malignant bone lesions. The above findings are consistent with the existing literature [ 12 , 13 , 14 ]. It is pertinent to mention here that though the levels were increased in both benign and malignant tumors, an increase in levels was not found statistically significant in benign bony lesions (p>0.05).…”
Section: Discussionsupporting
confidence: 94%
“…MDA levels were raised in both benign and malignant bone tumors as compared to healthy controls, though the rise in levels was more significant in malignant bone lesions. The above findings are consistent with the existing literature [ 12 , 13 , 14 ]. It is pertinent to mention here that though the levels were increased in both benign and malignant tumors, an increase in levels was not found statistically significant in benign bony lesions (p>0.05).…”
Section: Discussionsupporting
confidence: 94%
“…Tumor cells have a greater oxidative state, which increases the generation of ROS [ 32 ]. In addition, large amounts of reactive oxygen species may boost antioxidant activity in patients with stomach cancer [ 33 ]. Past studies have found a rise in CAT activity in patients with tumors [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The roles of oxidative stress in cancer are very perplexing due to variable cancer settings, distinct intensity and duration of oxidative stress, as well as specific stages of cancer evolution [ 24 ]. A prospective study shows that oxidative stress in patients with GC and their first-degree relatives significantly increased compared to dyspeptic patients [ 27 ], indicating that elevated oxidative stress probably contributes greatly to gastric carcinogenesis. Helicobacter pylori infection evokes long-lasting oxidative stress, which, in turn, fosters malignant transformation through various mechanisms [ 28 ].…”
Section: Discussionmentioning
confidence: 99%